Impulse flashover characteristics of oil palm trunk (OPT) veneer plywood - Gomes A.; Lim E.Y.; Islam T.; Parida M.T.; Choo A.C.Y.; Juliana A.H.; Gomes C.; Gomes A.E.; Kadir M.Z.A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adhesives; Electric breakdown; Electric insulators; Flashover; Hardwoods; Lightning; Lightning protection; Plywood; Roofs; Veneers; Wood products; Contaminated surfaces; Electrical breakdown; Fibre orientation; High voltage; Impulse flashover; Oil palm trunks; Surface flashover; Up-and-down method; Palm oil